The prediction of land use and land cover change and its impact on soil erosion and sedimentation in the Musi Hydropower-Plant catchment area in Bengkulu Province - Sukisno Sukisno; Widiatmaka Widiatmaka; Moh. Yanuar Jarwadi Purwanto; Bambang Pramudya Noorachmat; Khursatul Munibah (Journal of Degraded and Mining Lands Management, 2023)
The Musi Hydropower-Plant catchment area is susceptible to soil erosion and sedimentation. Therefore, this research aimed to predict land use and land cover changes (LULCC) as well as their impact on soil erosion and sedimentation in the Musi Hydropower-Plant catchment area. The prediction of LULCC was calculated using Land Change Modeler module on IDRISI Terrset, while soil erosion and sedimentation were estimated with the Revised Universal Soil Loss Equation (RUSLE) and Sediment Delivery Ratio (SDR) models. The result showed that forest cover and paddy fields decreased significantly from 18.580 ha and 4.044 ha to 12.907 ha and 2.019 ha, respectively, in the periods of 1993 to 2019 and were predicted to reduce until 2032. Meanwhile, the built-up area and dry agricultural land increased from 818 ha and 2.116 ha in 1993 to 2.229 ha and 5.778 ha in 2019, which is expected to increase until 2032. The estimation of soil erosion rate also gave an increase from 75 t/ha/year to 113 t/ha/year, continuing to reach 122 t/ha/year until 2032. The escalation of soil erosion rate contributed to the change of sediment yield from 68.048 t/year in 1993 to 103.190 t/year in 2019,which is estimated to reach 111.028 t/year. These results are expected to be used by decision-makers and policymakers for the operation of the Musi Hydropower-Plant and the catchment area maintenance.